Hubungan usia dan pengetahuan dengan persepsi petugas kesehatan terhadap vaksinasi Covid-19 - Yunus, Muhammad; Alfarisi, Ringgo; Hermawan, Dessy; Megarahayu, Soelastika (JOURNAL OF Community Health Issues, 2024)
Background : Covid-19 is an infectious disease caused by the SARS-CoV-2 virus, and is declared a pandemic. The Covid-19 outbreak is spreading very fast. The development of a Covid-19 vaccine is an approach to dealing with the SARS-CoV-2 outbreak. From the Covid-19 vaccination program carried out, perception is fundamental to the acceptance and assessment of the vaccinations carried out. There are several factors that can influence perception including internal factors, external factors, functional factors (knowledge, age), situational factors, structural factors, and personal factors. Purpose: This study aims to determine the relationship between age and knowledge with the perception of health workers on Covid-19 vaccination in Cilamaya Kulon District, Karawang Regency. Methods: This type of research uses quantitative analytical research with a cross sectional approach. The sample used is health workers who work in the work area of Cilamaya Kulon District, Karawang Regency with as many as 87 people. Result: The percentage of health workers with positive perceptions is 52.9%. Health workers aged less than 45 years were 67.8%. And good knowledge of 52.9%. Based on the Chi-Square test, the relationship between age and perception of the Covid-19 vaccination obtained a P value of 0.436. Meanwhile, on the relationship between knowledge and perception of Covid-19 vaccination, a P value of 0.612 was obtained. Conclusion :There was no relationship between age and perception of Covid-19 vaccination and there was no relationship between knowledge and perception of Covid-19 vaccination in health workers. Keyword: Covid-19; Knowledge; Perception; Healthcare Workers; Age; Covid-19 Vaccination.   Pendahuluan: Covid-19 penyakit menular yang disebabkan oleh virus SARS-CoV-2, dan dinyatakan sebagai pandemi. wabah Covid-19 menyebar sangat cepat. Pengembangan vaksin Covid-19 menjadi pendekatan untuk mengatasi wabah SARS-CoV-2.Dari program vaksinasi Covid-19 yang dilakukan, persepsi merupakan hal mendasar atas peneriman dan penilaian terhadap vaksinasi yang dilakukan. Terdapat beberapa faktor yang dapat mempengaruhi persepsi diantaranya faktor internal, faktor eksternal, faktor fungsional (pengetahuan, usia), faktor situasional, faktor struktural, dan faktor personal. Tujuan: Untuk mengetahui hubungan usia dan pengetahuan dengan persepsi petugas kesehatan terhadap vaksinasi Covid-19 di Kecamatan Cilamaya Kulon Kabupaten Karawang. Metode: Jenis penelitian ini menggunakan penelitian kuantitatif analitik dengan pendekatan cross sectional. Sampel yang digunakan adalah petugas kesehatan yang bekerja di wilayah kerja Kecamatan Cilamaya Kulon Kabupaten Karawang dengan sebanyak 87 orang. Hasil :Persentase petugas kesehatan dengan persepsi positif sebanyak 52,9%. Petugas kesehatan yang berusia kurang dari 45 tahun sebanyak 67,8%. Dan pengetahuan yang baik sejumlah 52,9%. Berdasarkan uji Chi-Square hubungan usia dengan persepsi terhadap vaksinasi Covid-19 didapatkan nilai Pvalue 0,436. Sedangkan pada hubungan pengetahuan dengan persepsi terhadap vaksinasi Covid-19 didapatkan nilai P value 0,612. Simpulan: Tidak terdapat hubungan antara usia dengan persepsi terhadap vaksinasi Covid-19 dan tidak terdapat hubungan antara pengetahuan dengan persepsi terhadap vaksinasi Covid-19 pada petugas kesehatan. Kata Kunci: Covid-19; Pengetahuan; Persepsi; Petugas Kesehatan; Usia; Vaksinasi Covid-19.